The Role of Insulin Regulated Aminopeptidase in Endocytic Trafficking and Receptor Signaling in Immune Cells - Descamps, Delphyne; Evnouchidou, Irini; Caillens, Vivien; Drajac, Carole; Riffault, Sabine; van Endert, Peter; Saveanu, Loredana (Frontiers in Molecular Biosciences, 2020)
Insulin Regulated AminoPeptidase (IRAP) is a type II transmembrane protein with broad tissue distribution initially identified as a major component of Glut4 storage vesicles (GSV) in adipocytes. Despite its almost ubiquitous expression, IRAP had been extensively studied mainly in insulin responsive cells, such as adipocytes and muscle cells. In these cells, the enzyme displays a complex intracellular trafficking pattern regulated by insulin. Early studies using fusion proteins joining the IRAP cytosolic domain to various reporter proteins, such as GFP or the transferrin receptor (TfR), showed that the complex and regulated trafficking of the protein depends on the cytosolic domain of the enzyme. This domain contains several motifs involved in IRAP trafficking, as demonstrated by mutagenesis studies. Also, proteomic studies and yeast two-hybrid experiments showed that the IRAP cytosolic domain engages in multiple protein interactions with cytoskeleton components and vesicular trafficking adaptors. These findings led to the hypothesis that IRAP is not only a cargo of GSV but might be a part of the sorting machinery that controls GSV dynamics. Recent work in adipocytes, immune cells, and neurons confirmed this hypothesis and demonstrated that IRAP has a dual function. Its carboxy-terminal domain located inside endosomes is responsible for the aminopeptidase activity of the enzyme, while its amino-terminal domain located in the cytosol functions as an endosomal trafficking adaptor. In this review, we recapitulate the published protein interactions of IRAP and summarize the increasing body of evidence indicating that IRAP plays a role in intracellular trafficking of several proteins. We describe the impact of IRAP deletion or depletion on endocytic trafficking and the consequences on immune cell functions. These include the ability of dendritic cells to cross-present antigens and prime adaptive immune responses, as well as the control of innate and adaptive immune receptor signaling and modulation of inflammatory responses.